A low‐cost real‐time face tracking system for ITSs and SDASs. (3rd October 2016) - Liu, Leyuan; Chen, Jingying; Gao, Changxin; Sang, Nong
Summary: It is important to track people's face efficiently and accurately in many Intelligent Transportation Systems (ITSs) and Safety Driving Assistant Systems (SDASs). This paper presents a high‐performance and low‐cost real‐time face tracking system, which runs on general onboard computer with very low CPU consumption. The proposed face tracking system is composed of four modules: the motion detector, face detector, face tracker, and face validator. The motion detector extracts motion areas by using a spatial‐temporal bi‐differential method with a very low computational cost. The face detector integrates motions into a cascade face detection framework to reject most of non‐face scanning‐windows to ensure efficient face localization. The face tracker fuses motion feature with color feature to alleviate the drifting problem during tracking. The face validator builds face appearance models online and identifies each specific tracked face to avoid confusion. Experimental results on three challenging video sequences show that the proposed face tracking system outperforms the state‐of‐the‐art face tracker and consumes only 5–13% CPU resources of a low‐spec onboard computer while processing in real time. Copyright © 2016 John Wiley & Sons, Ltd.